Thunbergia laurifolia Leaf Extract Increased Levels of Antioxidant Enzymes and Protected Human Cell-Lines In Vitro Against Cadmium - Marasri Junsi; Chutha Takahashi Yupanqui; Worapong Usawakesmanee; Alan Slusarenko; Sunisa Siripongvutikorn (MDPI AG, 2020)
Thunbergia laurifolia or Rang Jued has been used as an herbal tea and in folk medicine as a detoxifying agent. Cd contamination is globally widespread and a serious public health problem. The aim of this study was to determine the endogenous antioxidant enzyme activities and malondialdehyde (MDA) production of the crude dried extract (CDE) of T. laurifolia leaves, using human embryonic kidney (HEK293) and human liver (HepG2) cells as in vitro models. Moreover, the cytotoxicity including anti-cadmium (Cd) toxicity in both cells were measured. The experimental design had 3 treatment groups with combined, pre-, and post-treatments for investigating the anti-Cd toxicity, and cell viability was determined with MTT test (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide). The CDE showed low cytotoxicity and increased catalase (CAT) and glutathione peroxidase (GPx) activities with decreased malondialdehyde (MDA) levels in both cell types. It was found that the CDE protected against Cd-induced toxicity in both cell types, and a synergistic combination therapy effect was seen when CaNa2EDTA, a chelating agent, was applied. Therefore, CDE can protect against Cd-induced oxidative stress in cells, possibly due to its antioxidant properties. Moreover, using the extract or drinking the herbal tea together with chelating agent should have an efficacy advantage over using the CDE or the chelating agent singly.